2018
DOI: 10.3847/1538-4357/aaacd5
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Fluid Compression and Shear in Electron Energization during Magnetic Reconnection

Abstract: Particle acceleration in space and astrophysical reconnection sites is an important unsolved problem in studies of magnetic reconnection. Earlier kinetic simulations have identified several acceleration mechanisms that are associated with particle drift motions. Here, we show that, for sufficiently large systems, the energization processes due to particle drift motions can be described as fluid compression and shear, and that the shear energization is proportional to the pressure anisotropy of energetic partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 56 publications
5
83
0
Order By: Relevance
“…9b and d show that the extrapolated density values at the reconnection site (i.e., n e (d = 0)) vary by at least a factor of two, suggesting a high level of density inhomogeneity of δn e /n e > 100%. One of the possible causes is strong plasma compression at the reconnection site, which may facilitate electron acceleration through a Fermi-type mechanism (Provornikova et al 2016;Li et al 2018). The observation of tens of fast electron beams produced from an extremely compact region within a very short, <50 ms time scale is consistent with the bursty magnetic reconnection scenario (Kliem et al 2000;Drake et al 2006;Aschwanden 2002): The reconnection site is highly inhomogeneous and fragmentary, consisting of many fine dynamic structures such as magnetic islands and fractal currents.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…9b and d show that the extrapolated density values at the reconnection site (i.e., n e (d = 0)) vary by at least a factor of two, suggesting a high level of density inhomogeneity of δn e /n e > 100%. One of the possible causes is strong plasma compression at the reconnection site, which may facilitate electron acceleration through a Fermi-type mechanism (Provornikova et al 2016;Li et al 2018). The observation of tens of fast electron beams produced from an extremely compact region within a very short, <50 ms time scale is consistent with the bursty magnetic reconnection scenario (Kliem et al 2000;Drake et al 2006;Aschwanden 2002): The reconnection site is highly inhomogeneous and fragmentary, consisting of many fine dynamic structures such as magnetic islands and fractal currents.…”
Section: Discussionmentioning
confidence: 80%
“…However, here we are able to attribute such the 10km-scale fine structures directly to individual reconnection null points thanks to our ultra-high-cadence radio imaging data. We note that spatial scales at kilometer-level in the corona is now readily accessible by state-of-the-art kinetic or hybrid numerical simulations (Egedal et al 2012;Li et al 2018). Observational constraints derived at such fine spatial scales would undoubtedly shed new light on understanding the detailed reconnection-driven particle acceleration processes.…”
Section: Discussionmentioning
confidence: 92%
“…By evaluating relative contributions of the pressure tensor work and the fluid compression (shown in with the contribution from the non-ideal electric field. Li et al (2018) discussed the role of fluid compression and shear in electron energization in detail. They also find that fluid compression is the most important contributor in the pressure tensor term.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our result, though both the simulation setup and analysis methods are different than our study. Whereas Li et al (2018) considered only the perpendicular energization J ⊥ · E ⊥ associated with the perpendicular velocity and electric field, we consider the total energization J · E is considered. The parallel energization that is unaccounted for the pressure work is due to the non-ideal electric field.…”
Section: Discussionmentioning
confidence: 99%
“…Particle energisation mechanisms include parallel drift (Gordovskyy & Browning 2012), Fermi reflection of particles from the shortening magnetic field line (Hoshino 2012;Dahlin et al 2014), and betatron acceleration in the perpendicular direction (Fu et al 2011;Wang et al 2016a), etc., under the guiding-centre approximation. They could be linked to fluid compression (Zank 2014;Li et al 2018) and shear effects (le Roux et al 2015;Li et al 2018) in the fluid description. Further studies have shown a remarkable consistency between particle energisation in 2.5D and 3D simulations, as the dominant contribution to the particle acceleration might be the same (Hesse et al 2001;Zharkova et al 2011;Guo et al 2014;Dahlin et al 2017).…”
Section: Introductionmentioning
confidence: 99%